2019
DOI: 10.15632/jtam-pl/111909
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical parametric study of resistance spot welding process of AISI 1008 steel sheets

Abstract: In the present research, a parametric study in Resistance Spot Welding (RSW) of thin AISI 1008 steel sheets is investigated via FEM. All the time steps through the RSW process, including squeeze time, welding time, holding time and cooling time are taken into account. First, the effects of various parameters such as electrical current, welding time and electrode tip diameter are investigated in the nugget geometry. Then, a time history stress diagram and residual stresses are obtained in RSW weldment. FEM resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Figs. 18a and 19a, it was observed that maximum temperature reached about 1068 °C and 974.5 °C during the welding phase, respectively, which was lesser than the melting point temperature of DH36 steel [60] and AISI 1008 steel [61]. Hence, it is confirmed that the FSW is a solidstate welding process.…”
Section: Microstructure and Mechanical Propertiesmentioning
confidence: 72%
“…Figs. 18a and 19a, it was observed that maximum temperature reached about 1068 °C and 974.5 °C during the welding phase, respectively, which was lesser than the melting point temperature of DH36 steel [60] and AISI 1008 steel [61]. Hence, it is confirmed that the FSW is a solidstate welding process.…”
Section: Microstructure and Mechanical Propertiesmentioning
confidence: 72%